Microblogging in higher education: a comparative study - Mirabolghasemi, Marva; Noorminshah A. Iahad; Choshaly, Sahar Hosseinikhah (Penerbit Universiti Kebangsaan Malaysia, 2017)
Microblogging has become an increasingly popular phenomenon in educational context. There is currently little research regarding the educational advantages of microblogging dedicated to teaching and learning. Although educational microblogging provides great learning applications that can support formal learning environment, the advantages of these websites are oftentimes ignored. In order to investigate the largely unexplored benefits of educational microblogging, this research offers an opportunity to investigate the effect of microblogging using Community of Inquiry (CoI) model in a blended learning. The researchers used pre-questionnaire and post-questionnaire for evaluating the level of students' teaching, social and cognitive presence before and after using microblogging based on the CoI model. The questionnaires were distributed in two classes of 107 students in Universiti Teknologi Malaysia. Through statistical analysis by using t-test analysis, the usage of microblogging is proven to enhance students' cognitive, social and teaching presence. The results of this research offer an insight to the positive impact of the use of microblogging in higher education and its outcomes would open the door to new ways of learning and the nature of cooperative culture and new application tools.